2024
DOI: 10.3389/fbioe.2024.1347811
|View full text |Cite
|
Sign up to set email alerts
|

New strontium-based coatings show activity against pathogenic bacteria in spine infection

Daniele Ghezzi,
Gabriela Graziani,
Martina Cappelletti
et al.

Abstract: Infections of implants and prostheses represent relevant complications associated with the implantation of biomedical devices in spine surgery. Indeed, due to the length of the surgical procedures and the need to implant invasive devices, infections have high incidence, interfere with osseointegration, and are becoming increasingly difficult to threat with common therapies due to the acquisition of antibiotic resistance genes by pathogenic bacteria. The application of metal-substituted tricalcium phosphate coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In [16], the inhibition of bacterial growth was reduced due to the presence of the apatite-type phase, known for its lower solubility. The minimal concentration of Sr 2+ in β-TCP that exhibited effective antibacterial activity was found at x = 0.35 in Ca 10.15 Sr 0.35 (PO 4 ) 7 [26]. Importantly, this concentration did not induce cytotoxic effects [47].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In [16], the inhibition of bacterial growth was reduced due to the presence of the apatite-type phase, known for its lower solubility. The minimal concentration of Sr 2+ in β-TCP that exhibited effective antibacterial activity was found at x = 0.35 in Ca 10.15 Sr 0.35 (PO 4 ) 7 [26]. Importantly, this concentration did not induce cytotoxic effects [47].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, it was shown that Sr-doped β-TCP scaffolds promote early angiogenesis [24]. Sr 2+ ions prevented the formation of biofilms [25] without exhibiting cytotoxicity for mesenchymal stem cells [26].…”
Section: Introductionmentioning
confidence: 99%